The criteria of establishing the demand for information specialists - Augustinaitis, Arūnas; Macevičiūtė, Elena (Information & Media, 1996)
The Faculty of Communication of Vilnius University has started surveying the need for information specialists in Lithuania according to a joint project with the Tallinn Pedagogical University. The article deals with three main issues: the definition of the concept "information specialist"; trends in the training of information specialists in Lithuania; the definition of the area, ways, and statistical basis of the survey.